Risk of cardiovascular diseases in psoriasis – the current state of knowledge - Wójcik-Maciejewicz, Anna; Sawińska, Edyta; Reich, Adam (Dermatology Review/Przegląd Dermatologiczny, 2019)
Psoriasis is a chronic recurrent inflammatory disease that may limit physical and psychosocial functioning as well as decrease the quality of life of the sick. Until recently, psoriasis has been considered a disease that involves the skin and joints only. Latest studies have showed that psoriasis is associated with a considerably higher risk of cardiovascular events, such as myocardial infarction or stroke. Moreover, a more frequent occurrence of risk factors specific for cardiovascular diseases, including arterial hypertension, diabetes, dyslipidaemia, obesity, and metabolic syndrome, is confirmed in a group of psoriatic patients. As a consequence, mortality rates in patients with psoriasis are higher, and their life expectancy is shorter as compared to the general population. Existing inflammation, dysfunctional adipokine secretion, insulin resistance, increased angiogenesis, and oxidative stress constitute a pathogenetic foundation for the link between psoriasis and cardiometabolic diseases. Given the above, patients with psoriasis should be screened for the metabolic syndrome and cardiovascular diseases, also modification of risk factors specific to these diseases should be aimed at.